Answer:
The fraction is =
Step-by-step explanation:
In simplest form the fraction is represented in mixed number as .
The fraction form of the mixed number can be given as :
Let the fraction be = [As multiplying same numbers to numerator and denominator does not affect the proportion.
Sum of numerator and denominator is = 30
This, can be represented as:
Solving for .
Dividing both sides by 10.
So, the fraction will be =
⇒
Answer:
A) 0.265
B) 0.0265
C) 0.837
D) 0.0837
E) 0.00265
F) 0.00837
Step-by-step explanation:
We are given;
√7 = 2.65 and √70 = 8.37
A) √0.07 can be rewritten as;
√(7 × 1/100)
Let's deal with the digits in the bracket.
Square root of 100 is 10. Thus;
√(7 × 1/100) = (1/10)√7 = (1/10) × 2.65 = 0.265
B) √0.0007
Rewrite to get;
√(7 × 1/10000)
Square root of 1/10000 is 1/100
Thus;
√(7 × 1/10000) = (1/100)√7 = (1/100) × 2.65 = 0.0265
C) √0.7
Like above;
√0.7 = √(70 × (1/100))
>> (1/10)√70 = (1/10) × 8.37 = 0.837
D) √0.007
Like above;
Rewrite to get;
√(70 × 1/10000)
Square root of 1/10000 is 1/100
Thus;
√(70 × 1/10000) = (1/100)√70 = (1/100) × 8.37 = 0.0837
E) √0.000007
Rewritten to;
√(7 × (1/1000000))
√(1/1000000) = 1/1000
Thus; √(7 × (1/1000000)) = 1/1000 × √7 = 1/1000 × 2.65 = 0.00265
F)√0.00007
Rewritten to;
√(70 × (1/1000000))
√(1/1000000) = 1/1000
Thus; √(70 × (1/1000000)) = 1/1000 × √70 = 1/1000 × 8.37 = 0.00837
Answer:
∠EFH = 21°
∠HFG = 62°
∠EFG = 83°
Step-by-step explanation:
The diagram showing the angles has been attached to this response.
From the diagram, it can be deduced that;
Angle EFG = angle EFH + angle HFG
=> ∠EFG = ∠EFH + ∠HFG -------------------(i)
From the question:
∠EFH = (5x + 1)° -------------(ii)
∠HFG = 62° -------------(iii)
∠EFG = (18x + 11)° -------------(iv)
<em>Substitute these values into equation (i) as follows;</em>
(18x + 11) = (5x + 1) + 62
=> 18x + 11 = 5x + 1 + 62
<em>Collect like terms and solve for x</em>
18x - 5x = 1 + 62 - 11
13x = 52
x = 4
Now, to get each measurement, substitute x = 4 into each of equations (ii) - (iv)
∠EFH = (5x + 1)°
∠EFH = (5(4) + 1)°
∠EFH = (20 + 1)°
∠EFH = 21°
∠HFG = 62° [<em>Does not depend on x</em>]
∠EFG = (18x + 11)°
∠EFG = (18(4) + 11)°
∠EFG = (72 + 11)°
∠EFG = 83°
<u>Conclusion:</u>
∠EFH = 21°
∠HFG = 62°
∠EFG = 83°
Answer:
4230 apples
Step-by-step explanation:
5190-960=4230
Answer:
x^2 -20x + 100
Step-by-step explanation:
How this works is that you multiply each number by every other number, so.
(x+a)(x+b) so you do x times x since the parenthesis multiplies them together. Then you do x times b.
Then you do a times x since a is the next number in the first pair. then you do a times b.
(* is the sign for multiplication for the sake of simplifying it and to be easier than doing something like x x x where you are multiplying x together with x.)
So in the expression (x + a)(x + b) you are basically doing
x * x + x * b + a * x + a * b
In your case, a is = to -10 and b is equal to -10
So your expression would be
x * x + x * -10 + -10 * x + -10 * -10
so x times x is x^2 and x times -10 is -10x You are doing -10 * x twice so it is -20x and -10 times -10 is 100
So the final equation would be x^2 plus -20x plus 100 or
x^2 + (-20x) + 100
which is
x^2 -20x + 100
Hope this helps!